1985
DOI: 10.1111/j.1532-5415.1985.tb05437.x
|View full text |Cite
|
Sign up to set email alerts
|

Copper and Zinc Levels in “Healthy” and “Sick” Elderly

Abstract: Healthy elderly as a group have a wider range for serum copper, ceruloplasmin, and serum zinc than the adjusted ranges for the laboratory. In disease serum copper and/or ceruloplasmin act as acute-phase reactants in vascular disease, inflammation, and malignancy. Serum zinc values likewise are affected by the presence of inflammation and malignancy. The reported low level of copper in patients with osteoporosis was not confirmed by the present study. Neither was there any evidence found for zinc deficiency in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…In contrast, however, Mutlu et al [6] did not find any difference in the concentration of copper between the serum of osteoporotic and healthy subjects. Similar results to those of Mutlu et al [6] were also obtained by Kotkowiak [7] and Murphy et al [8], while Massie et al [9] have shown that copper was negatively correlated with bone Ca concentrations. Consequently, Massie et al [9] have suggested that excess copper was the single most important factor associated with decreasing bone size and density.…”
Section: Introductionsupporting
confidence: 89%
“…In contrast, however, Mutlu et al [6] did not find any difference in the concentration of copper between the serum of osteoporotic and healthy subjects. Similar results to those of Mutlu et al [6] were also obtained by Kotkowiak [7] and Murphy et al [8], while Massie et al [9] have shown that copper was negatively correlated with bone Ca concentrations. Consequently, Massie et al [9] have suggested that excess copper was the single most important factor associated with decreasing bone size and density.…”
Section: Introductionsupporting
confidence: 89%
“…Several studies reported that serum Zn and Cu levels were lower among patients with postmenopausal osteoporosis than controls [25-27]. In contrast, Reginster et al [16] significant difference in Zn and Cu plasma levels between two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies [25-27] in postmenopausal women have been shown lower nail Ca concentrations than in premenopausal women. Their BMD status showed a significant positive correlation with nail Ca content.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc is essential for life and reproduction and is a component of the cell nucleus, mitochondria, cytoplasm, cell membranes, and cell walls [99]. Zinc is a constituent of about 300 enzymes, and Zn ions are located in the catalytic site as well as in the structural site of the enzyme complex [100,101]. …”
Section: Overview Of Brushite-forming Mg- Zn- and Sr-substituted mentioning
confidence: 99%